Application of selected Lean tools in the improvement of work safety in the use of machinery - Małysa Tomasz (Production Engineering Archives)
The issue of safety in the use of machinery is an important issue for both manufacturers and employers. The current legislation imposes a number of obligations on manufacturers (essential requirements) and employers (minimum requirements) related to ensuring safety at every stage from design to operation. The study analyzes the possibility of applying selected Lean Manufacturing tools to improve occupational safety in the use of machinery (work equipment). The purpose of the study is to present the possibility of application of selected LM tools on operator safety, as well as to meet the requirements of legislators relating to safety related to the use of machinery. Implemented LM solutions improve communication and organization of work, and most importantly, reduce the risks associated with the operation of machinery and equipment.